Echoes of devotion: Okokan in Tabanan as ritual sound, social cohesion, and Balinese spiritual life - Ni Wayan Sadiyani; M. Agus Sutiarso; Firman Sinaga; Jumhur Hakim; Asma Khan; Chet Narayan Acharya; Dr. Nirdosh Kumar Agarwal; Md. Alaul Haque; Tijjani Ahmed Ajayi (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2026)
The Tektekan Okokan tradition of Kediri, Tabanan, is a surviving Balinese ritual using sonic instruments—Okokan, Kulkul, and Tengteng—to repel disease outbreaks (grubug) and neutralize negative forces in the village. Historically performed for days or even months following spiritual messages (pawisik) and signs of occult disturbance, today it is mainly held on Pengerupukan, the eve of Nyepi, as a replacement for ogoh-ogoh processions while circling the village. This practice inspires the creation of a contemporary fashion collection. Data on the tradition were obtained through literature study, observation, and documentation. The design process follows the eight‑stage Frangipani method (design brief; research and sourcing; design development; final collection; prototype, sampling, and construction; promotion, branding, and sales; production; and business). The resulting works comprise three categories—ready to wear, ready to wear deluxe, and haute couture—visualizing Tektekan Okokan through selected keywords and plague‑like, enveloping motif details that symbolically depict the village under attack and ritually protected.